Development of a rapid and accurate system to differentiate malaysian honey samples using UV and color image / Abd Alazeez Al-Maleeh. - Al-Maleeh, Abd Alazeez (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2016)
The main goal of this project is to provide an alternative method to allow the different types of honey to be classified. Also, it presents a fusion of the two methods implemented to improve the classification accuracy. The objectives of this project are as follow ; to classify the origin of honey using antioxidant level by measuring the wavelengths from UV-Vis Spectroscopy ; to classify the origin of honey based on the colour of honey images captured by Digital Camera ; to implement data fusion technique by combining both UV and Digital Image for honey classification ; to evaluate the performance of the fusion and compared with single method.